Comparison of the effectiveness of pilates exercises, aerobic exercises, and pilates with aerobic exercises in patients with rheumatoid arthritis - Yentur, Songul Baglan; Atas, Nuh; Ozturk, Mehmet Akif; Oskay, Deran (Springer London Ltd, 2021)
Background Rheumatoid arthritis (RA) is a rheumatic disease characterized by erosive synovitis and polyarthritis. Exercise is known to improve many symptoms in RA patients. Aim This study was designed to compare the effects of pilates exercises, aerobic exercises, and combined training including pilates with aerobic exercises on fatigue, depression, aerobic capacity, pain, sleep quality, and quality of life. Methods Thirty voluntary RA patients were included in this study. Patients were divided into three groups equally, and treatment was applied to each group for 8 weeks. Pilates exercises were practiced to the first group, aerobic exercises were practiced to the second group, and combined training was performed to the third group. Fatigue, depression, aerobic capacity, pain, sleep quality, and quality of life were evaluated using Fatigue Severity Scale (FSS), Beck Depression Inventory (BDI), 6-minute walk test (6MWT), McGill Pain Questionnaire- Short Form (MPQ-SF), Pittsburg Sleep Quality Index (PSQI), and Rheumatoid Arthritis Quality of Life (RAQoL), respectively. Results The results of the present study showed significant improvements for the first group on fatigue, depression, aerobic capacity, and quality of life (p < 0.05). Improvements in all parameters except for pain were obtained for the second and third groups (p < 0.05). In addition, there was no statistically significant difference among the treatment groups in assessments (p > 0.05). Conclusion Pilates exercises may have similar effects to aerobic exercises in patients with RA. Addition of clinical pilates exercises to the routine treatment of RA may enhance the success of rehabilitation. Trial registration NCT03836820
Keywords: Aerobic exercises; Fatigue; Pilates exercises; Rheumatoid arthritis